Modelling and Simulation of Disc Brake Contact Analysis and Squeal - Abu Bakar, A. R.; Ouyang, H.; Titeica, D.; Hamid, M. K. A. (UNIVERSITI KEBANGSAAN MALAYSIA, 2005)
Predicting disc brake squeal by means of the complex eigenvalue method has been a popular approach in the brake research community owing to its advantages over the dynamic transient method. The positive real parts of the complex eigenvalue reflect the degree of instability of the brake system and are thought to indicate the likelihood of squeal occurrence. This paper studies the disc brake squeal using a detailed 3-dimensional finite element (FE) model of a real disc brake. A number of structural modifications for suppressing unstable vibration are simulated. Influence of contact pressure distribution on squeal propensity is also investigated. A plausible modification that results in reduced positive real parts of the eigenvalues is proposed.